Environmental Risk and Toxicity Effect of Organophosphorus Insecticides on Male Red Earthworm (Eisenia foetida) (International Journal of Medical and Surgical Sciences, 2015)
Organophosphate pesticides are widely used to eliminate pests in agriculture. In Arica- Chile, they were used to control and eliminate the plague of fruit fly (Ceratitis capitata). They act as acetylcholinesterase inhibitors and induce DNA damage. The aim of this study was to analyze the effects of malathion and methamidophos two organophosphate pesticides on male reproductive parameters of red earthworm Eisenia foetida. After determining the LD50 in mg per kilogram of soil (malathion= 880 mg/kg and methamidophos= 85.3 mg/kg), we proceeded to subdue Eisenia foetida at a dose of 1/10, 1/6, 1/3 and 2/3 of the LD50. The control groups were sprayed with water. All groups were analyzed at 1, 6, 15 and 30 days post treatment. The weight and external morphological changes was determined. Sperm count was held in camera Neubaur, DNA integrity was determined with Acridine orange test. The Ethics / Bioethics Committee at the University of Tarapaca, approved the research protocols. The results show that both organophosphate express a significant decrease in body weight in all animals treated with 100% of coiled tail. A significant rise in the number of sperm at 1, 6 and 15 days followed by a significant decrease from 15 to 30 days was observed. A significant increase of abnormal metachromatic sperm (red fluorescence) in all treated animals was observed. It is concluded that malathion and methamidophos, alter the external morphology, sperm count and quality of Eisenia foetida red earthworm. The use of these chemicals needs better handling and storage procedures to avoid altering human health and the environment.